Clinical features and risk factors of primary peritonitis in children with primary nephritic syndrome - DING Juan-juan; WU Yan-xiang; LUAN Jiang-wei (Linchuang shenzangbing zazhi)
Objective To analyze the clinical characteristics and risk factors of primary nephrotic syndrome(NS) complicated with spontaneous bacterial peritonitis(SBP) in childrea Methods The clinical data of 7 children with NS complicated with SBP in our hospital from January 2000 to January2014 were retrospectively studied.T-test was used to compare the data between groups,and P<0.05 was considered statistically significant.Results The patients were male with age ranging from 6 years and 2 months to 10 years old.The course of nephrotic syndrome was 7 days to 2 years and 9 months.The clinical symptoms of SBP included abdominal pain,nausea,vomiting,diarrhea,fever,and important signs were peritoneal irritation.For laboratory tests,Alb was(12.54 ±2.45) g/L,and IgG was(1.97 ± 0.54) g/L,which decreased obviously.The cytological examination of ascites showed that the amounts of WBC were significantly increased,and the number of the polymorphonuclear white blood cells was significantly increased,and the ascites protein was positive.Two patients were ascites culture positive(one case of Escherichia coli,and one case of Hemolytic streptococcus).Abdominal CT scan showed abnormal image.After anti-infective therapy and supportive care(gamma globulin,albumin,plasma),6 cases were cured(infection symptoms disappeared,and ascites subsided),and 1 case gave up.In the long-term follow-up period,the nephritic syndrome was alleviated in 3 cases and prednisone was withdrawn;2 cases obtained remission and were still treated;1 case had the steroid resistance and obtained no remission.Conclusions NS complicated by SBP in children was insidious onset,and rapid progress for severe infections.Ascites cytology and abdominal CT examination are important auxiliary means.Men and hypoalbuminemia are high risk factors for peritonitis.For NS children with massive ascites,once gastrointestinal symptoms occur,the SBP should be alert.Through actively and full course anti-infection treatment,and supportive treatment(albumin,globulin protein and/or plasma),we can obtain satisfactory effectiveness.